Interface shear characteristics of dredger fill and concrete using large size direct shear test - Ping Yang; Shou-Bao Xue; Li Song; Ming-shi Duan (International Journal of Geo-Engineering, 2018)
Abstract A large-size direct shear test was conducted to test the interface of dredger fill and concrete. The effect that concrete strength and the density of dredger fill have on the properties of interface is then analyzed. Digital photography was used to record soil particles of dredger fill moving near the interface, and the particle images were analyzed by particle image velocimetry technique. The results of the tests show that the shear strength of interface fit the model laid out in the Mohr–Coulomb theory. The relationship between shear displacement and shear stress fit the hyperbola model. Soil particles of dredger fill near the interface have large horizontal displacement and obvious vertical displacement of the particles. Under high normal stress, concrete strength has significant influences on the shear strength of interface. Density of dredger fill has great effects on the shear strength of interface.